Auditor Selection Determinants in the Banking Sector of UK and Uzbekistan - Tursunova, Farangiz (2011)
This study investigates the relationship between auditor choice and commonly used client firm characteristics in a sample of UK and Uzbekistan Banks. The basis of the research constitutes that, banks with different characteristics demand varying level of audit quality. Therefore, objective of this thesis is to identify the association of audit characteristics, client characteristics and auditor characteristics on the banks choice of external auditors ( Big four versus local or second tier audit firms). Data was collected from the annual reports of sample banks in UK and questionnaire survey was conducted in Uzbekistan. For testing of the hypothesis, Logistic regression is used. The results show that corporate governance issues such as independence of board of directors and internal complexity of the banks were found to have significant relationship on the choice of high quality auditors. Contrary to agency theory estimates, the results show that banks with increased in leverage levels are less likely to select Big Four auditors. Additionally, the audit fees were expected to the most significant determinant of new auditor choice, while the result was contrary to initial expectations. Few variables were significant in the model of new auditor choice and the outcomes are explained in the Chapter 5. Finally, The results of the conducted survey in Uzbekistan present the important variables associated with the choice of Big Four auditors. It was found that, banks with foreign shareholders and international clients are more likely to hire Big four audit firms. However, in contrast with UK banks results, in Uzbekistan the audit fee has significant influence on the choice of quality auditors.